DEVELOPMENT OF AUTODESK INVENTOR PROFESSIONAL 2022 TEACHING MATERIALS IN COMPUTER-AIDED ENGINEERING-BASED MECHRONIC SYSTEMS COURSES AT THE MECHRONIC EXPERTISE PROGRAM AT SMKN 8 MALANG - Prameisthy Dyah Anggraeni Isnodo; Purnomo Purnomo; Duwi Leksono Edy (UNIVERSITAS SRIWIJAYA, 2023)
The world of education in the 4.0 era is required to apply learning according to technology. One of them is the Mechatronics System Based on Computer Aided Engineering (SMBCAE) in the Mechatronics Expertise Program at SMKN 8 Malang which is required to be able to operate a professional Autodesk inventor to draw digitally. This trains students to solve design problems in a project. This study aims to develop teaching materials as study guides that are varied and contain materials including initial concepts, 2D sketches, 3D models, and assembly of the Autodesk Inventor 2022 application. The development of these teaching materials uses the Borg & Gall development model. The validation, which consisted of one media expert validator and two material expert validators, showed that the module was feasible to develop. In addition, based on the results of product trials conducted on 60 students, the results were 82.5%. Thus it can be categorized that the teaching material is very good and feasible to use